Praktik Pembatasan Internet Pada Masa Konflik di Papua - Silas, Jonah; Agustino, Leo; Hikmawan, M Dian (HK-Publishing, 2024)
AbstrakThis research explores the practice of internet restrictions carried out by the state, with a focus on the current socio-political conflict situation. Digital power as a concept is used in this research to look at state control over the internet, especially when socio-political conflicts occur, and the internet becomes a threat to state stability. This research focuses on state control of the internet in the practice of internet restrictions when social conflict is ongoing in Papua. Qualitative research was conducted using a case study approach, using literature studies and interviews with government institutions and private institutions that are related to the issue of internet restrictions. The main finding of this research is that the practice of internet restrictions carried out by the state during the conflict in Papua was to prevent the public from verifying the accuracy of information.Keywords: Â Internet Restrictions, Digital Power, Conflict in Papua.Â AbstrakPenelitian ini mengeksplorasi praktik pembatasan internet yang dilakukan oleh negara, dengan fokus pada situasi konflik sosial politik yang sedang terjadi. Kuasa digital sebagai konsep digunakan pada penelitian ini untuk melihat kendali negara pada internet, terkhusus ketika konflik sosial politik terjadi dan internet menjadi ancaman bagi stabilitas negara. Penelitian ini fokus pada kontrol negara dalam internet pada praktik pembatasan internet ketika konflik sosial sedang berlangsung di Papua. Penelitian kualitatif dilakukan dengan pendekatan studi kasus, menggunakan studi Pustaka dan wawancara dengan lembaga pemerintah serta lembaga swasta yang memiliki keterkaitan dengan isu pembatasan internet. Temuan penelitian ini yang utama ialah, praktik pembatasan internet dilakukan oleh negara pada masa konflik di Papua ialah untuk menghambat publik melakukan verifikasi keakuratan informasi.Kata kunci: Pembatasan Internet, Kuasa Digital, Konflik di Papua.